ANALISIS KETERAMPILAN MENGAJAR MAHASISWA PADA MATA KULIAH MICRO TEACHING PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH - Muksal Mina Putra; Tika Meldina; Agus Riyan Oktori; Susilawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the teaching skills of students in the Micro Teaching Course in the Study Program of Madrasah Ibtidaiyah Teacher Education IAIN Curup. This research conducted in descriptive quantitative approach to analyze the teaching skills of Semester 6 students who are taking Micro Teaching Courses. The results showed that: 1). opening and closing skills are in the “good” category. 2). Students' skills in explaining are in the “very good” category. 3). Basic and advanced questioning skills are in the “good” category. 4). The skill of giving reinforcement is in the “good” category. 5). The skill of organizing variations is in the “good” category. 6). Classroom management skills are in the “good” category. 7). Small group and individual teaching skills are in the “very good” category. 8). Skills in guiding group discussions are in the “not good” category. Overall student teaching skills are in the “good” category.